Assessing site significance : a guide for archaeologists and historians - Hardesty, Donald L., 1941- (Heritage resources management series., 2009)
Assessing Site Significance is an invaluable resource for archaeologists and others who need guidance in determining whether sites are eligible for listing in the National Register of Historic Places (NRHP). Because the register's eligibility criteria were largely developed for standing sites, it is difficult to know in any particular case whether a site known primarily through archaeological work has sufficient "historical significance" to be listed. Hardesty and Little address these challenges, describing how to file for NRHP eligibility and how to determine the historical significance of ar.